Pendidikan Pesantren dalam Membentuk Kompetensi Santri - Saefumillah, Sansan (Edukasi: Journal of Educational Research, 2021)
This paper describes the education applied by the Fathul Ulum Islamic boarding school Kwagean Kediri to form the competence of students. This research is a field research using qualitative methods and a case study approach. This study found that in shaping the intellectual competence of students, the Fathul Ulum Islamic boarding school used four methods, namely bendongan/serogan, bahsul masa'il or discussion, ubudiyah or seminars, and lalaran or memorization. Meanwhile, in shaping the career competencies of students, the Fathul Ulum Islamic boarding school has a pesantren economic institution called the Pesantren-Owned Business Entity (BUMP), this business entity is fully managed by the students